2018
DOI: 10.1002/ldr.3029
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditive effects of biochar amendments on soil phosphorus fractions in two contrasting soils

Abstract: Increased soil total phosphorus (P) or available P has been reported in biochar‐amended soils, although the underlying mechanisms need to be fully understood. In the present study, two contrasting soils (acidic Haplic Luvisol and alkaline Calcaric‐Fluvisol) amended with wheat straw biochar were sequentially extracted with modified Hedley method to study the P transformation in the soils. Our results showed that biochar application significantly increased (positive effects) P fractions (except for NaHCO3‐Pi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(52 reference statements)
5
15
1
Order By: Relevance
“…In contrast to the positive impact on soil-available P described previously, especially in acidic soils, it has been shown that biochar with low P content can reduce P availability in soils [72], through increasing P sorption capacity promoted by surface area increase [81] and in metal oxides and carbonates [82] derived from biochar, through immobilisation of P by stimulating microbial activity [80,83] and by means of precipitation of stable phosphate minerals in alkaline soils [65].…”
Section: Change In the P Fixation Mechanism In Soils By Biochar Amendmentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast to the positive impact on soil-available P described previously, especially in acidic soils, it has been shown that biochar with low P content can reduce P availability in soils [72], through increasing P sorption capacity promoted by surface area increase [81] and in metal oxides and carbonates [82] derived from biochar, through immobilisation of P by stimulating microbial activity [80,83] and by means of precipitation of stable phosphate minerals in alkaline soils [65].…”
Section: Change In the P Fixation Mechanism In Soils By Biochar Amendmentioning
confidence: 66%
“…Thus, soil P fixation increases in alkaline soils amended with biochar through precipitation of Ca-P minerals and P sorption onto calcite in alkaline soils due to additional input of alkaline elements such as Ca, which is often contained in biochar [63]. In general, biochar had no effect on P sorption isotherms in alkaline soils, especially in soils with high P sorption capacity [63,80].…”
Section: Change In the P Fixation Mechanism In Soils By Biochar Amendmentioning
confidence: 99%
“…Biochar decreased the activity of acid phosphomonoesterase but increased the activities of alkaline phosphomonoesterase (responsible for mineralization of organic P), indicating that biochar may affect related microorganisms and their released enzymes by increasing soil pH (Jin et al 2016). Xu et al (2018a) showed that biochar application significantly increased fractions of H 2 O-soluble and NaOH-extractable inorganic P, and NaHCO 3 -extractable organic P, but decreased the NaHCO 3 -extractable inorganic P fraction. This indicated that biochar addition assists microorganisms to solubilize the fixed P and increases microbial P immobilization.…”
Section: Soil Microbial-mediated P Cyclingmentioning
confidence: 98%
“…A better method is to apply organic amendments to raise organic matter amount of the salt‐affected soil (Montiel‐Rozas, Panettieri, Madejón, & Madejón, ; Oo, Iwai, & Saenjan, ; Reed, Chadwick, Hill, & Jones, ; Veneklaas et al, ). Different types of organic amendments such as green manures, farmyard and poultry manures, compost, food‐processing wastes, and biochar have been applied to soils for enhancing soil quality (Bhaduri et al, ; Liu et al, ; Xu, Zhang, Shao, & Sun, ; Yang, Bian, Tang, Zhou, & Li, ). Among these, green manure is a promising way with long‐term effects and low cost (Bai et al, ; Bai, Xu, et al, ; Bai, Yan, et al, ; Bai, Zou, et al, ; Li et al, ; Maltas, Kebli, Oberholzer, Weisskopf, & Sinaj, ; Meier et al, ; Xu et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%